Cost-effective screening strategy to prevent venous thromboembolism in combined oral contraceptive users - Douxfils, Jonathan (Frontiers in Endocrinology, 2025)
Venous thromboembolism (VTE), encompassing deep vein thrombosis (DVT) and pulmonary embolism (PE), is a leading cause of global morbidity and mortality, with a significant societal and economic burden. Combined oral contraceptives (COCs) increase VTE risk by 2- to 6-fold, resulting in approximately 22,925 cases annually in the European Economic Area (EEA). Despite the high associated healthcare costs, which may reach 2.5 billion EUR annually, current international guidelines, including those from the World Health Organization (WHO) and the Faculty of Sexual and Reproductive Healthcare (FSRH), discourage routine thrombophilia screening prior to COC prescription, citing low cost-effectiveness, low prevalence of thrombophilia, and potential unintended consequences, such as reduced contraceptive use. Recent advancements in screening technology challenge these guidelines. The normalized Activated Protein C sensitivity ratio (nAPCsr) assay, a low-cost tool capable of detecting both inherited thrombophilia and acquired COC-induced activated protein C (APC) resistance, offers a promising strategy for targeted screening. Economic models estimate that implementing nAPCsr-based screening could prevent up to 13,500 VTE cases annually, leading to 1.5 billion EUR in annual healthcare savings. Additionally, nAPCsr-guided contraceptive counseling enables personalized decision-making, directing high-risk women toward safer contraceptive options, such as progestin-only pills or COCs containing natural estrogens (estradiol or estetrol), which present a lower thrombotic risk. This manuscript emphasizes the necessity of updating current prevention strategies by integrating innovative screening tools like the nAPCsr assay. By addressing both direct healthcare costs and indirect costs related to productivity loss and long-term complications, such a strategy could improve patient safety, reduce the financial burden on healthcare systems, and promote equitable access to safer contraceptive methods. Furthermore, targeted screening could alleviate the underrepresentation of high-risk women in current cost estimates and significantly mitigate the societal impact of COC-associated VTE. In light of these findings, reconsidering current policy recommendations appears essential to facilitate evidence-based, cost-effective prevention of COC-related thrombotic events, ultimately enhancing public health outcomes.